Continuous production of honey oligosaccharides in packed-bed reactors with immobilized α-glucosidase from Metschnikowia reukaufii. (January 2023) - Garcia-Gonzalez, Martin; Narmontaite, Egle; Cervantes, Fadia V.; Plou, Francisco J.; Betancor, Lorena; Fernandez-Lobato, Maria
Abstract: The α-glucosidase from the yeast Metschnikowia reukaufii, a producer of honey sugars, was immobilized on chitosan beads and biomimetic silica nanoparticles under mild and green conditions. Chitosan based derivatives showed apparent activities of about 40–70 U·g −1, while silica entrapped enzyme nanoparticles contained 486 U·g −1 . Compared to the soluble enzyme, the immobilized biocatalysts showed maximum hydrolytic activity at higher temperatures and broader pH interval, in addition to an excellent batch operational stability, maintaining 75–90% of its initial activity after ten subsequent cycles of 20 min reactions. Furthermore, chitosan beads and silica nanoparticles biocatalysts were packed into reactor columns and for the first time employed in the continuous overproduction of isomelezitose and trehalulose. Both systems operated continuously for 30 days with excellent isomelezitose yields of about 62 and 54% of the total sugar synthesised, respectively. The bioreactor based on chitosan beads had an average productivity of 0.5 kg L −1 per day. This production was increased by almost 10 times (4.9 kg L −1 per day) when a micro-reactor based on the biomimetic silica nanoparticles was used. Consequently, this work constitutes an interesting approach for the production of isomelezitose on an industrial scale, a new high-value functional sugar with interesting applications. Highlights: M. reukaufii α-glucosidase was immobilized and applied in honey bioconversions. The biocatalysts were morphologically and biochemically characterised. The immobilized enzyme exhibited good reusability and stability for hetero-GlcOS synthesis. Immobilized biocatalysts continuously produced bioactive hetero-GlcOS in PBRs for 30 days.